Roles of ARID1A variations in colorectal cancer: a collaborative review - Shankun Zhao; Weizhou Wu; Zufu Jiang; Fuqin Tang; Lingzhi Ding; Weifang Xu; Libin Ruan (BMC, 2022)
Abstract Colorectal cancer (CRC), a common malignancy, is one of the leading cause of cancer death in adults. AT-rich interaction domain 1A (ARID1A), a critical portion of the SWItch/sucrose non-fermentation (SWI/SNF) chromatin remodeling complexes, shows one of the most frequent mutant genes across different human cancer types. Deleterious variations of ARID1A has been recognized to be correlated the tumorigenesis and the poor prognosis of CRC. Here, we summarize recent advances in the clinical implications and molecular pathogenesis of ARID1A variations in CRC. According to independent data of 23 included studies, ARID1A is mutated in 3.6-66.7%. Consistently, all of the 23 relevant studies report that ARID1A functions as a specific tumor suppressor in CRC. Clinically, ARID1A variation status serves as a biomarker for survival prognosis and various therapies for CRC. Mechanistically, the pathophysiologic impacts of ARID1A variations on CRC may be associated with the co-occurrence variations of other genes (i.e., TP53, KRAS, APC, FBXW7, and PIK3CA) and the regulation of several signaling pathways being affected (i.e., WNT signaling, Akt signaling, and MEK/ERK pathway), leading to cell cycle arrest, chromatin remodeling, chromosome organization, and DNA hypermethylation of the cancer cells. The present review highlights ARID1A serving as a potent tumor suppressor and an important prognostic factor in CRC. ARID1A variations hint towards a promising tool for diagnostic tumor profiling and individualized therapeutic targets for CRC in the future.